Physical activity at home to improve strength and balance in the elderly to prevent the risk of falls. Bibliographic Review - Paredes, Alisha Narjeel Morales (2024)
The main objective of this research work was to conduct a review of the effectiveness of strength and balance exercise programs in preventing falls in older adults. To this end, a collection process was carried out mainly from the PubMed and Sciencedirect databases, selecting the journals with the greatest impact. The sample consists of 29 articles selected considering the following variables: year of publication, objectives, sample, instruments, and conclusions. The results showed that most of the studies were developed in 2021, the main objective of 16 of them was to identify an effective physical exercise program at home for the prevention of the risk of falls in older adults, the age of the population was over 60 years, the most used instrument was the Timed Up and Go, and 93.1% of the articles conclude that a home exercise program contributes to increased strength and improved balance, reducing the potential risk of falls. Finally, it is concluded that the use of previously established programs or multicomponent programs are effective based on their accessibility, economy, capacity, and quality of these, in addition to being able to do it remotely, so the use of digital platforms such as Facebook or YouTube is quite useful.